Collaborative Action on Fetal Alcohol Spectrum Disorder Prevention: Principles for Enacting the Truth and Reconciliation Commission Call to Action #33 - Wolfson, Lindsay; Poole, Nancy; Ninomiya, Melody Morton; Rutman, Deborah; Letendre, Sherry; Winterhoff, Toni; Finney, Catherine; Carlson, Elizabeth; Prouty, Michelle; McFarlane, Audrey; Ruttan, Lia; Murphy, Lisa; et al. (International Journal of Environmental Research and Public Health, 2019)
The association between fetal alcohol spectrum disorder (FASD), residential schools and subsequent assimilatory policies in Canada is of such significance that it was included in the groundbreaking Truth and Reconciliation Commission of Canada’s Final Report through Call to Action #33, which focuses on collaboratively developing FASD prevention programs in Indigenous communities. A consensus statement with eight tenets for enacting Call to Action #33 was co-developed in May 2017 using a Two-Eyed Seeing approach during and after a meeting on Indigenous approaches to FASD prevention held in Canada. The consensus statement provides guidance for creating community-based, culture-led FASD prevention programs in Indigenous communities. The eight tenets reflect the diverse perspectives of Indigenous and non-Indigenous participants, are grounded in available research evidence, and align with Indigenous worldviews and wellness models. This paper uses the consensus statement and eight exemplary FASD prevention programs from Indigenous communities and organizations across Canada to highlight identity, culture, and relationships as central elements of FASD prevention in Indigenous communities. The consensus statement provides guidance for developing community- and culture-led FASD prevention programs and highlights the importance of Indigenous knowledge systems in developing and researching FASD prevention in, and with, Indigenous communities. The Dialogue to Action on the Prevention of FASD was supported by a Canadian Institute for Health Research (CIHR) Planning and Dissemination Grant—Institute Community Support [#150430], with additional financial support from the First Nation and Inuit Health Branch (FNIHB). This research was supported by the Social Sciences and Humanities Research Council of Canada. SSHRC ref.: 612 2018-0187. Faculty Reviewed